-6+8(x+4)=-6x+2(x+7)

Simple and best practice solution for -6+8(x+4)=-6x+2(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+8(x+4)=-6x+2(x+7) equation:



-6+8(x+4)=-6x+2(x+7)
We move all terms to the left:
-6+8(x+4)-(-6x+2(x+7))=0
We multiply parentheses
8x-(-6x+2(x+7))+32-6=0
We calculate terms in parentheses: -(-6x+2(x+7)), so:
-6x+2(x+7)
We multiply parentheses
-6x+2x+14
We add all the numbers together, and all the variables
-4x+14
Back to the equation:
-(-4x+14)
We add all the numbers together, and all the variables
8x-(-4x+14)+26=0
We get rid of parentheses
8x+4x-14+26=0
We add all the numbers together, and all the variables
12x+12=0
We move all terms containing x to the left, all other terms to the right
12x=-12
x=-12/12
x=-1

See similar equations:

| (X+3/2)-(3x-1/4)=1 | | 3(x+2)+5=4 | | 30x6-0.6=10.24 | | 5(2x+4)-4x=44 | | h=30T-0.6 | | 4x+6x-44=66-9x | | 2(2x-3)+6x=24 | | 20x+5=2x-13 | | 0.13x+0.7(x-5)=0.01(2x-5) | | 1,2x+15=15 | | 7.71=2(3.14)r | | 2(x+4)+3=-5(x+1) | | (x+4)^2=225 | | 162=6(x-2) | | 17+2,5x=32 | | 4p-p=5-2 | | 175m−100m+48,750=50,500−175m | | x+1/6x=25 | | 12x^2-x-426=0 | | |x-4|+|2x-1|=|x|+3 | | 12-|x-3.5|=19 | | 5(2x-3)=6-5x | | 7+y/3=10 | | 12=3(x+6)-6x | | 2+3×-6=x+3 | | 4w+6÷2=19 | | X+7+x×3=47 | | 3x-6=2x+24 | | 4/5b+2/15=8/3b | | |2x-6|=18 | | 2(3×-6)=x+3 | | 2(2x-4=20 |

Equations solver categories